Partisipasi Trinitaris Dalam Penyembahan: Rekonstruksi Makna “Dalam Roh Dan Kebenaran” Berdasarkan Yohanes 4:20–26 - Setiawan, Eko Agus; Siagian, Johannes Hotlan Harsono; Pasaribu, George Rudi Hartono (LPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
John 4:20–26 is often read as a contrast between outward ritual and inward sincerity, or as evidence that Christian worship is no longer related to place, the body, or liturgical form. Although such readings capture part of the passage, they may reduce the phrase “spirit and truth” to personal authenticity. This study reexamines the theological meaning of worship in spirit and truth by bringing together the Gerizim–Jerusalem controversy, Johannine Christology and pneumatology, and contemporary Pentecostal theology of worship. Employing qualitative theological research through a focused literature review, narrative-exegetical analysis, and canonical-theological synthesis, the study argues that Jesus does not simply abolish sacred geography. Rather, he centers worship on himself within the eschatological “hour” inaugurated through his person and work. Worship “in spirit” describes a human response awakened and sustained by the Holy Spirit, while worship “in truth” means conformity to God’s self-revelation embodied in Christ and witnessed in Scripture. The article’s main contribution is a trinitarian-transformative participation model: the Father seeks worshipers, the Son mediates and gives worship its definitive shape, and the Spirit enables the church to respond. Such participation must take visible form in the life of the church and produce ethical, reconciling, and missional fruit. Therefore, Pentecostal and contemporary worship should be assessed not mainly by emotional intensity, musical style, or technological sophistication, but by its Christ-centered character, the integration of Spirit and Word, communal discernment, and its ability to form a holy and witnessing people.